Quartz‐Based Cantilevers: Soft‐Chemistry‐Assisted On‐Chip Integration of Nanostructured α‐Quartz Microelectromechanical System (Adv. Mater. Technol. 3/2021). Issue 3 (8th March 2021) - Jolly, Claire; Gomez, Andres; Sánchez‐Fuentes, David; Cakiroglu, Dilek; Rathar, Raïssa; Maurin, Nicolas; Garcia‐Bermejo, Ricardo; Charlot, Benoit; Gich, Martí; Bahriz, Michael; Picas, Laura; Carretero‐Genevrier, Adrian
Abstract : In article number 2000831, Adrian Carretero‐Genevrier and co‐workers develop epitaxial nanostructured α‐quartz micro‐cantilevers on silicon, through the combination of soft‐chemistry and top‐down approaches for piezoelectric sensor devices. The α‐quartz MEMS show excellent force and mass sensitivity while preserving the mechanical quality factor. Additionally, the α‐quartz patterned micro‐cantilevers are biocompatible, which rendered cell adhesion and proliferation equivalent to that of conventional glass coverslips.